IoT-Based Monitoring System for Smart Agriculture to Enhance Crop Yield Efficiency - Pham Van Anh; Tran Minh Tuan; Nguyen Duc Thang; Quang Anh Tuan; Kentaro Fujimura (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study investigates an IoT architecture for smart agriculture that combines event-triggered sensing with edge-level multi-sensor fusion to reduce energy consumption across distributed sensor networks. While prior research has largely focused on optimizing individual node efficiency, our findings reveal that the primary source of energy savings arises from systemic behavioral changes within the network’s communication ecology. Real-world experiments on a multi-node deployment show that edge fusion reduces redundant transmissions, stabilizes medium-access contention, and significantly extends sleep intervals. Collectively, these effects produce an average 30% reduction in wake-up frequency, even in relay nodes that do not perform fusion. The results indicate that the underlying mechanism is ecological rather than local: by lowering network-wide communication turbulence, the system achieves a more stable, low-activity state, allowing overlapping dormancy clusters to form naturally. This challenges the long-standing assumption that energy efficiency must be pursued primarily at the node level. Limitations include the controlled experimental environment, moderate network scale, and potential latency risks in time-critical scenarios. The study’s theoretical contribution lies in reframing energy-efficient IoT design as a complex adaptive systems problem, where efficiency emerges from interactions across the network rather than isolated node behavior. This ecosystem-centric perspective opens new directions for sustainable IoT architectures. Future research should focus on designing protocols, topology strategies, and fusion mechanisms that deliberately shape systemic behavior in IoT networks, aiming to achieve greater efficiency, resilience, and longevity than node-centric approaches alone.